Burkina Faso : Second Review Under the Three-Year Arrangement Under the Extended Credit Facility and Request for Modification of Performance Criteria: Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burkina Faso. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
This study discusses how Burkina Faso's economy recovered from the 2009 downturn. Recent economic and social developments used to overcome the 2009 downturn are explained. Discussions on fiscal policy and mitigating measures against exogenous shocks, external sector policies and reforms, and prospects for accelerated growth under the new Poverty Reduction Strategy Paper (PRSP) are focused in this paper. The performance of the program will be monitored by structural benchmarks and quantitative targets. Finally, the conclusion of the second Extended Credit Facility (ECF) review and medium-term policy was recommended by IMF staff.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet